2011
DOI: 10.1007/s12011-011-9249-9
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Expression of Selenoprotein N Transcripts in Chicken Tissues and Early Developmental Expression Pattern in Skeletal Muscles

Abstract: Previous results revealed a ubiquitous expression pattern of selenoprotein N (SelN, SEPN1) in humans, zebrafish, and mouse, suggesting that it plays a potential role during the embryogenesis of these species. However, no information is known about the tissue distribution of SelN and mRNA expression analysis in the muscle tissues during development in birds. We analyzed the mRNA expression of SelN in 26 different tissues of 90-day-old chickens and the expression of SelN in the muscle tissues of 12-day-old chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Different levels of expression were observed in the brain, liver, spleen, testis, thyroid, as well as in cardiac and skeletal muscles [ 11 ]. Selenoproteins, such as GPX s, were found to express in the liver, kidney, and muscle [ 5 ], whereas SELW and SELN mRNA transcripts were detected in various kinds of tissues, especially more abundant in muscles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different levels of expression were observed in the brain, liver, spleen, testis, thyroid, as well as in cardiac and skeletal muscles [ 11 ]. Selenoproteins, such as GPX s, were found to express in the liver, kidney, and muscle [ 5 ], whereas SELW and SELN mRNA transcripts were detected in various kinds of tissues, especially more abundant in muscles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this additional exon 3 appeared to be primate specific and later analyses indicated that the second isoform, in which exon 3 is spliced out, is the most abundant in cells and the only one to be translated into protein (Petit et al 2003). Screening for SELENON mRNA revealed its expression in many tissues, including skeletal and cardiac muscles, though at different levels (Lescure et al 1999;Castets et al 2009;Zhang et al 2012).…”
Section: Molecular Description Of Selenon Gene and Protein: Expressio...mentioning
confidence: 99%
“…Suboptimal selenoprotein levels upregulate inflammatory cytokines [ 24 ], leading to muscle weakness and oxidative damage [ 25 ]; higher levels of interleukin 6 (IL-6) have been associated with low selenium status [ 26 , 27 ]. IL-6 can impact muscle function and contraction as it interferes with insulin-like growth factor 1 (IGF-1) secretion [ 28 , 29 , 30 ] and is also involved in bone resorption and receptor activator of nuclear factor kappa-Β ligand (RANK-L) signalling [ 31 , 32 , 33 , 34 ]. Likewise, muscle function can be impaired; selenium-deficient patients had elevated levels of serum creatine kinase, muscle fatigue, pain, and proximal weakness [ 2 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%